DP Smart Belt: innovative accessory for adaptive tennis athletes with electronic device integration - García-Betancur, Paola Andrea (2025)
This research presents the development of an electronic accessory designed for wheelchair tennis athletes. The study was conducted using an applied methodology, combining qualitative and quantitative approaches in equal proportions according to the study’s objectives. The research had an exploratory scope and was carried out with a population of eleven (11) Olympic wheelchair tennis players, affiliated with the Institute of Sports, Education, and Recreation (INDERVALLE) in the city of Santiago de Cali. A simple sampling method was employed, considering the specific characteristics of individuals practicing the activity under the mentioned condition. The primary data collection instrument was direct observation. The innovative accessory, hereafter referred to as the “DP Smart Belt,” consists of a belt incorporating electronic technology, programmed to measure displacement and rotational frequencies during physical activity, thereby obtaining information to generate effort statistics over periods of time. With this implementation, the “DP Smart Belt” offers the possibility of improving physical conditioning by providing acceleration measurements, which can be uniaxial or triaxial. Uniaxial measurement occurs in a single direction (vertical), while triaxial measurement covers three directions (anteroposterior, mediolateral, and longitudinal). These technological advancements have facilitated innovation and creativity in wearable accessories, enabling changes and providing crucial information about bodily behavior to enhance athletic performance. This is especially important for athletes who play wheelchair tennis, as they tend to experience physical wear, exhaustion, and a decrease in physical condition due to exceeding their maximum effort capacity.